DEVELOPMENT OF BISMUTH OXYCHLORIDE (BIOCL) PHOTOCATALYST FOR ORGANIC POLLUTANT DEGRADATION - Kiki Wulandari, Yuvita
Photocatalysis offers a promising solution to address water pollution due to its environmentally friendly and cost-effectiveness. BiOCl has emerged as a prominently researched material for organic pollutants degradation as a photocatalyst. Oxygen vacancies (OVs) and facet exposure play a crucial role in enhancing photocatalyst performance. Various efforts have been made to modify or engineer materials to achieve the desired characteristics. pH control is one of the important factors in material synthesis. Currently, there are limited studies that examine the influence of precursor pH on the optical properties, morphology, and crystallinity of BiOCl synthesized using the hydrothermal method, which is critical for further development of photocatalyst materials for targeted applications. XRD characterization results show that purephase BiOCl formed at pH 5, pH 7, and pH 10. At strong acidic condition, a mixture of BiOCl and Bi24O31Cl10 phases is formed, while at highly alkaline pH levels, the phase shifts to Bi2O3. This indicates that the optimal pH for forming pure BiOCl is at pH 5, pH 7, and pH 10. Additionally, the morphology of BiOCl consists of sheets with nanometer-scale thickness. FTIR characterization reveals that BiOCl is composed of Bi-O bonds (541 cm?¹) and Bi-Cl bonds (1037 cm?¹ and 1351 cm?¹). These results are further supported by XPS characterization, which shows that the surface of the BiOCl sample is composed of Bi 4s, O 1s, and Cl 2p atoms. Further analysis using CasaXPS reveals the presence of OVs in each BiOCl sample with varying pH, with the highest concentration of OVs found in BiOCl at pH 7. Additionally, Bi-O, Bi-OH, and H2Oads bonds, as well as Cl atoms in different states, are present in all samples. The synthesized samples were tested for their photocatalytic performance for degrading rhodamine B (RhB) and bisphenol A (BPA). The results of the photocatalytic assessments demonstrate that BiOCl at pH 7 exhibits a remarkable degradation rate of 98.67% towards RhB. Moreover, evaluations at different pH levels indicate that proximity to neutral pH corresponds to higher degradation rates, diminishing as pH becomes more alkaline. The photocatalytic test on BPA also shows performance consistent with the RhB test results, although BPA is more challenging to degrade, with the most optimal performance at pH 7 being 44.86%. The strong photocatalytic performance is closely related to the role of OVs and facet exposure in the synthesized photocatalyst material.